Leading with Compassion in Times of Change - Muhammad Taufiq Amir (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
Managers face various challenges and difficulties at work, especially in dealing with changes. The adverse events can be compounded when personal problems also put additional pressure on the manager. The compassionate leader can function to alleviate the stress. This study shows how leading with compassion, where leaders are sensitive to problems, feeling those difficulties, and are motivated to help. By referring to the positive organization literature, aspects, and processes of compassion in organizations are disclosed. Likewise, how compassionate leaders increase the attention and understanding, empathize with the needs of managers and their future are also explained. Furthermore, leaders can also be present in the various policies that they create. This study is useful for making leadership effective, especially in managing organizational change.